2019
DOI: 10.1080/01932691.2019.1631841
|View full text |Cite
|
Sign up to set email alerts
|

The role of medium on the assembly of carbon nanotube by dielectrophoresis

Abstract: Dielectrophoresis (DEP) is an electrode-medium process used to control the movement of Carbon nanotubes (CNTs) within a solution under nonuniform electric fields. CNTs are typically dispersed into a solvent to form a homogeneous suspension in order to prevent their aggregation and to improve solubility. This paper starts with a short review of the techniques used to improve the compatibility of CNTs with a target medium. Then, direct and indirect variations in CNTs' velocities as a function of DEP force were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Several million devices were packaged in a square centimeter [61]. Recent studies concluded that the quality of aligned CNTs using DEP depends on many factors, such as the electrode design [62,63], suspension quality [64], and CNTs enrichment [65,66].…”
Section: Alignment By Electric Forcesmentioning
confidence: 99%
“…Several million devices were packaged in a square centimeter [61]. Recent studies concluded that the quality of aligned CNTs using DEP depends on many factors, such as the electrode design [62,63], suspension quality [64], and CNTs enrichment [65,66].…”
Section: Alignment By Electric Forcesmentioning
confidence: 99%
“…In DEP systems, applying an electric field inside the fluid creates significant forces other than the DEP force, which in turn generates fluid motion and alter the DEP manipulation of micro-and nanoparticles [52,53]. These forces, such as electrothermal force (ETF), EOF, and Brownian motion, are directly or indirectly affected by the conductivity of the media [54]. Thus, selecting the conductive medium is critical to ensure that the F DEP magnitude is larger enough to dominate these forces and prevent any unexpected particle motion or damage.…”
Section: Dep Mechanismmentioning
confidence: 99%
“…There are two routes to solve the joule heating problem or reduce its effects, such as the medium drag velocity. The first route is by optimizing the components of the DEP system, such as optimization of the medium electrical conductivity and the AC signal parameters [21,22]. However, this solution might not be enough because DEP suffers from high attenuation rates, where the velocity due to DEP force dramatically decreases as the distance from the electrode outer surface increases [23].…”
Section: Introductionmentioning
confidence: 99%